Psammobatis lentiginosa, Freckle Sandskate - Pollom, R. (2020)
The Freckle Sandskate (Psammobatis lentiginosa) is a small (to 55 cm total length) skate that occurs in the Southwest Atlantic from Rio Grande do Sul, Brazil to Chubut Province, Argentina. It inhabits the continental shelf at depths of 28-170 m. It is captured in demersal trawl fisheries, which are intense in parts of its range. Its small size and continued abundance in catches without evidence of a decline indicates that it may be productive enough to withstand some fishing pressure, and the population is suspected to be stable. Therefore, the Freckle Sandskate is assessed as Least Concern.